SUPERVISION SYSTEM BASED AGILE APPROACH ON PERFORMANCE MANAGEMENT IN THE HIGHER EDUCATION INSTITUTION (HEI): SYSTEMATIC LITERATURE REVIEW - Hafizhah Suzana Hussien; Armin Razita Bong Julita; Mohammad Haziq Mohd Johari; Zulkepli Mukhtar; Norshita Mat Nayan; Mujahid Abu Bakar; Mohamad Syahmi Shahril; Nur Farah Liza Ramli (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2024)
This paper aims to identify, review, and synthesize the supervision system based agile approach on performance management in the higher education institution (HEI) based on a systematic review. The present paper carried out a systematic literature review (SLR) of the related literature. An efficient survey was distinguished written works by electronic open access information base inquiries (Google scholar, Emerald insights and Science Direct). The inclusion criteria were: i) publication date between 2012 and 2022, ii) country, iii) methodology, iv) model/theory and v) dimension. The preferred reporting items statement was followed when performing narrative synthesis and systematic review using Preferred Reporting Items for Systematic Review and Meta-Analyses (PRISMA) search methodology strategy. Systematic literature review has been undertaken by identifying 1,307 studies from various sources. After removing the 1,296 studies based on selection criteria, 11 studies have been found relevant for the present study. The review suggests that the supervision system based agile approach is necessary to enhance performance of the HEI. This research found there is no standardised methodology to measure the supervision system based agile approach on performance management in the higher education institution. The study conceptualises a research model which can be used by the policymakers to develop model of supervision system for performance management.